1970
DOI: 10.1021/ja00711a018
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight boron sulfides. V. Vaporization behavior of the boron-sulfur system

Abstract: The vaporization behavior of the boron-sulfur system has been studied mass spectrometrically with a glassy, sulfur-rich B2S3 sample, a stoichiometric B2S3 sample, a stoichiometric B2S3 -Zn mixture, and a FeS-B-Zn mixture. Glassy B& gave the most intense and most complicated spectra; the stoichiometric BsS3 sample, the stoichiometric B2S3-Zn mixture, and the early stages of the FeS-B-Zn mixture gave, in the temperature range 400-650 O, indistinguishable spectra that were intermediate in intensity and complexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Early mass spectroscopic studies suggested that the cationic B 2 S 2 + cluster may be a precursor for high molecular weight clusters 40 . It is valuable to calculate the formation energy of the D 3 h B 3 S 3 + ( 1 ) cluster using linear B 2 S 2 + and BS species as reactants, according to the following equation: B 2 S 2 + ( D ∞ h , 2 ∑ g ) + BS ( D ∞ h , 2 ∑ g ) = B 3 S 3 + ( 1 , D 3 h , 1 A 1 ′).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early mass spectroscopic studies suggested that the cationic B 2 S 2 + cluster may be a precursor for high molecular weight clusters 40 . It is valuable to calculate the formation energy of the D 3 h B 3 S 3 + ( 1 ) cluster using linear B 2 S 2 + and BS species as reactants, according to the following equation: B 2 S 2 + ( D ∞ h , 2 ∑ g ) + BS ( D ∞ h , 2 ∑ g ) = B 3 S 3 + ( 1 , D 3 h , 1 A 1 ′).…”
Section: Resultsmentioning
confidence: 99%
“…Selected literature on binary B m S n clusters is surveyed here. In the 1960s and 1970s, mass spectroscopic studies in the gas phase confirmed the existence of a series of boron sulfide cations, suggesting that BS 2 + , B 2 S 2 + , and B 2 S 3 + are important precursors to form high molecular weight B‐S clusters 37–41 . Quite recently, computational works from us revealed rhombic B 2 S 2 and pentagonal B 3 S 2 rings in B 4 S 4 and B 3 S 2 H 3 clusters, respectively 42–44 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Due to the close similarity between S (3s 2 3p 4 ) and O (2s 2 2p 4 ) in valence electron configuration, the boron‐sulfur clusters have also been the focus of research interests 47–62, though the related data is much less than those of B m O n . Small boron sulfide species BS 2 + , B 2 S 2 + , B 2 S 3 + were already characterized by gas phase spectroscopy studies more than 30 years ago 52–55. The di/tri‐anionic BS 3 3− , B 2 S 4 2− , B 2 S 5 2− , B 3 S 6 3− have been found to exist as building blocks in materials 56.…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structure for B2S3 as proposed by Chen(41). Crystal structure of BjSj showing four-and six-membered rings.…”
mentioning
confidence: 99%